Effect of Individualized Head-Related Transfer Functions on Distance Perception in Virtual Reproduction for a Nearby Sound Source - YU, Guangzheng; WANG, Liliang (Archives of Acoustics, 2019)
The head-related transfer function (HRTF) is dependent on the position of the sound source (both direction and distance) and is also affected by individual anatomical parameters. Individualized HRTFs have been shown to affect the perception of sound direction, but have not been considered in distance perception. This work aims to discover, by means of psychoacoustic experiments for a virtual reproduction system through a pair of in-ear headphones, the effect of individualized HRTF on auditory distance perception for a nearby sound source. The individualized HRTFs of six subjects and the non-individualized HRTFs of a mannequin at seven distances between 0.2 and 1.0 m and five lateral azimuths between 45X and 135X in the horizontal plane were processed with white noise to generate binaural signals. Further, the individualized and non-individualized HRTFs were used in the auditory distance perception experiments. Results of distance perception show that the variance of distance perception results among subjects is significant, the reason could be the stimuli are lack of dynamic cue and early reflections, or the auditory difference of distance perception among subjects. However, via the analyses of mean slope of perceptual distance and correlation between the perceptual and real distance, we find that the individualized HRTF cue has insignificant influence on distance perception.